PENGARUH CAR, LDR, BOPO DAN KURS TERHADAP NON PERFORMING LOAN (NPL) (Studi Empiris Pada Bank Umum Konvensional yang terdaftar di Bursa Efek Indonesia Periode 2018-2021) - Putri, Chintya Kurnia; Darlis, Edfan; Supriono, Supriono (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2025)
This study aims to analyze (1) the effect of CAR on Non Performing Loans (NPL) (2) the effectof LDR on Non Performing Loans (NPL) (3) the effect of BOPO on Non Performing Loans(NPL) (4) the effect of the Exchange Rate on Non Performing Loans (NPLs).The population ofthis study are conventional banking companies listed on the Indonesia Stock Exchange for the2018-2021 period. In this study, the samples obtained were 40 companies obtained throughpurposive sampling. This study uses secondary data obtained from the annual reports ofconventional banking companies listed on the Indonesia Stock Exchange for the 2018-2021period and uses data from the Bank Indonesia website. The results of this study indicate thatCAR and BOPO have an effect on Non Performing Loans (NPL), while LDR and ExchangeRate have no significant effect on Non Performing Loans (NPL).Keywords: Non Performing Loan, Capital Adequacy Ratio, Loan to Deposit Ratio, OperatingExpenses Operating Income and Exchange Rate